PERAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KETERAMPILAN PEDAGOGIK DAN KINERJA DI SEKOLAH DASAR ISLAM MUNIRUL BILAD RANTAU PULUNG - Aspiati, Aspiati; Satriah, Saatriah (STAI Sangatta Kutai Timur, 2025)
This study examines the role of educational supervision in improving pedagogical skills and teacher performance at Munirul Bilad Islamic Elementary School. Educational supervision is understood as a systematic process encompassing monitoring, guidance, and evaluation to foster teacher professionalism. Findings indicate that effective supervision approaches can enhance teachers' pedagogical skills by 30%, as measured through classroom observation and peer feedback. Effective supervision also fosters a conducive learning environment, supports the integration of Islamic values, and improves student outcomes. The study recommends employing value-based supervision, technological advancements, and collaborative culture enhancement to address existing challenges.